2010
DOI: 10.17221/67/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical cycles of chlorine in the coniferous forest ecosystem: practical implications

Abstract: Chlorine -one of the most widespread elements on the Earth -is present in the environment as chloride ion or bound to organic substances. The main source of chloride ions is the oceans while organically bound chlorine (OCl) comes from various sources, including anthropogenic ones. Chlorinated organic compounds were long considered to be only industrial products; nevertheless, organochlorines occur plentifully in natural ecosystems. However, recent investigations in temperate and boreal forest ecosystems have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…The authors established in situ tracer experiments using chloride-37 and showed that after the addition of chloride-37 to soil, the formation of CH 37 Cl 3 was observed. Similar results were reported recently by Matucha et al (2010). The application of radioisotope tracers has to be considered as a sophisticated method to identify formation mechanisms of naturally produced chloroform.…”
Section: Introductionsupporting
confidence: 85%
“…The authors established in situ tracer experiments using chloride-37 and showed that after the addition of chloride-37 to soil, the formation of CH 37 Cl 3 was observed. Similar results were reported recently by Matucha et al (2010). The application of radioisotope tracers has to be considered as a sophisticated method to identify formation mechanisms of naturally produced chloroform.…”
Section: Introductionsupporting
confidence: 85%
“…The main natural terrestrial sources of VOCls so far identified are soil, salt marshes, rice fields, tropical forests, peatlands, temperate forest soil, litter, plants and fungi (Khalil et al 1998, Haselmann et were also found on average at 0-23.5 pmol/day/g DW and 0-13.5 pmol/day/g DW, respectively. High diversity of emissions can be found among different species (Table 1) and the inhomogeneity of soil is also well known (Matucha et al 2010). Living plants form VOCl for various purposes; defense mechanism against bacterial and fungal infection, deterrence of grazers, allelopathic interactions and accidental formation of biological by-products are mentioned most often (Mtolera et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The emissions of chloroform, tetrachloromethane or chloromethane from some marine and terrestrial sources, such as marine macroalgae, coastal salt marshes and forest soil are documented (Laturnus et al 1998, Rhew et al 2000, Hoekstra et al 2001, Svensson et al 2007). It has been suggested that chlorine contributes to the decay of soil organic matter (SOM) leading to the formation of large molecules of chlorohumus (Asplund 1995, Matucha et al 2010. Degradation of chlorohumus leads to smaller intermediates, such as chlorinated acetic acids, anisol-, orcinoland hydroquinone-based substances, which may be taken up by plants or fungi.…”
mentioning
confidence: 99%
“…Previous research has demonstrated that Clorg concentrations exceed Cl -levels in soil (Keppler & Biester, 2003;Biester et al, 2004;Svensson et al, 2007a) and that Clorg is produced naturally (Öberg et al, 2002). In boreal and temperate soils, 48% to almost 100% of the total Cl has been found as Clorg in the upper soil layers (Johansson et al, 2003a(Johansson et al, , 2003bSvensson et al, 2007;Matucha et al, 2010;Redon et al, 2011). This implies that Cl is highly reactive in soil and that Clorg transformation processes such as chlorination (Cl -becoming Clorg) and dechlorination (Clorg becoming Cl -) are important in the Cl cycle, as soil seems to act as both a source and a sink of Cl (Rodstedth et al, 2003).…”
Section: Introductionmentioning
confidence: 99%